Computer simulation of the working tool of the thermoelectric device for cryodesstruction taking into account the phase transition - Anatychuk, L.I.; Kobylianskyi , R.R.; Fedoriv, R.V. (Journal of Thermoelectricity, 2022)
The paper presents the results of computer modeling of the working tool of the thermoelectric device for cryodestruction, taking into account the phase transition, as well as the cyclic temperature effect on the human skin in dynamic mode. A physical model of the working tool, a three-dimensional computer model of biological tissue, taking into account thermophysical processes, blood circulation, heat exchange, metabolic processes and phase transition, were built. As an example, we consider the case when there is a working tool on the surface of the skin, the temperature of which changes cyclically according to a predetermined law in the temperature range [50 ÷ +50] °C. Temperature distributions in different layers of human skin in cooling and heating modes were determined. The obtained results make it possible to predict the depth of freezing and warming of biological tissue at a given temperature effect.